Electronic Health Record Adolescent Confidentiality in a Safety Net Setting - You, Jacqueline Guan-Ting; Potter, Julia Esther; Mishuris, Rebecca Grochow (Applied Clinical Informatics, 2023)
Background The 21st Century Cures Act provides improved access to one's medical record but presents new challenges to adolescent confidentiality in the domain of health care information technology. Adolescent patients, who have the right to confidential care in certain areas as dictated by state law, face the prospect of parents and guardians erroneously accessing their confidential health information.Objectives Our institution, the largest safety net hospital in our region, sought to quantify the proportion of adolescent patient portal accounts likely being accessed by guardians and to implement corrective measures for the patient portal sign-up process in our electronic health record (EHR) system.Methods We manually reviewed our institution's adolescent patient portal accounts based on email addresses associated with adolescents' accounts. We implemented EHR changes to address the potential for breach of confidentiality as a result of adolescent patient portal account creation by guardians. One intervention was creating a “guardrail rule” to prevent guardians from creating adolescent patient portal accounts with their own email addresses. After email reminders to adolescent patients to update their accounts, we deactivated accounts with concern for erroneous guardian access.Results Sixty percent of our institution's adolescent patient portal accounts had possible direct access by guardians. Following requests to update account access, 425 (18.8%) of accounts had email addresses updated by adolescent patients and 1,830 (81.2%) accounts were deactivated.Conclusion More nuanced EHR functionality for adolescent patients and their guardians can help health care systems provide confidential, patient-centered care for adolescents, while allowing guardians to access appropriate health information to facilitate care. There is an opportunity for a national consensus on how adolescents and their guardians can access health information by patient portal.
Keywords: adolescent medicine; confidentiality; patient portals; electronic health records; HIPAA; 21st Century Cures Act